Memoir of War Based on a Novel by Marguerite Duras - Duras, Marguerite (New Wave Films, 2019)
In the 1944 Nazi-occupied France, young Marguerite Duras is a talented writer and an active Resistance member with her husband Robert Antelme. When he is deported by the Gestapo, she dives into a desperate struggle to get him back. She develops a chilling relationship with local Vichy collaborator Rabier and takes terrible risks to save Robert, playing a cat-and-mouse of unpredictable meetings all over Paris. [www.amazon.co.uk]
Keywords: DVD-Video